Sifat Fisis dan Mekanis Baja Karbon Rendah dengan Perlakuan Carburizing Arang Tempurung Kelapa - Putra, Dika Ardi, Dr. Supriyono (2017)
Pack carburizing is the simple carburizing method, which it uses powder charcoal as addition of the carbon element. The purpose or carburizing research is to know the change of steel properties either physical or mechanical. The material that used is low carbon steel (mild steel) < 0.3%C. The carburizing process begins with mixing from coconut steel charcoal of 80% and NaCO3 of 20%, and then entered into the property with a specimen in the middle position. The continued, heating in the furnace with 980 C temperatures around two hours and then allowed to stand in the furnace until cold, the next in the test with Vickers method that uses micro hardness tested and observation of micro structure that uses inverted metallurgical microscope. The result of the hardness testing on the raw material has Vickers hardness with 183.817 VHN. Meanwhile, the hardness of the average objects after carburizing process with coconut shell charcoal is 309.614 NHN. So, the raw material after carburizing has been increased with quitehighuntil 68, 43%.